2020
DOI: 10.1589/jpts.32.206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between walking ability of patients with stroke and effect of body weight-supported treadmill training

Abstract: Reports on the amount of unloading maximizing walking ability in patients with stroke are limited. The effect of body weight-supported treadmill training (BWSTT) in patients with stroke has not been clarified. We aimed to investigate the effects of unloading rate during BWSTT on the gait of patients with stroke and the relationship between BWSTT and walking ability on flat ground. [Participants and Methods] We performed BWSTT in 17 patients at three unloading rates: 0%, 20%, and 40%. Then, we examined the walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As previous research indicated that BWSTT can improve left/right symmetry 10 ) , we also calculated the single leg stance time ratio as the index of symmetry, with improvement in this index being the primary outcome of a positive effect of BWSTT on post-stroke gait. In our previous study, the single leg support time ratio on level ground walking correlated with the rate of improvement in the BWSTT single leg support time ratio 6 ) . Therefore, we hypothesized that the ability to walk on level ground may be a predictor of the improvement in the single leg support time ratio by BWSTT.…”
Section: Participants and Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…As previous research indicated that BWSTT can improve left/right symmetry 10 ) , we also calculated the single leg stance time ratio as the index of symmetry, with improvement in this index being the primary outcome of a positive effect of BWSTT on post-stroke gait. In our previous study, the single leg support time ratio on level ground walking correlated with the rate of improvement in the BWSTT single leg support time ratio 6 ) . Therefore, we hypothesized that the ability to walk on level ground may be a predictor of the improvement in the single leg support time ratio by BWSTT.…”
Section: Participants and Methodsmentioning
confidence: 83%
“…The Biodex Unweighing System (NY, USA) was used for BWSTT, with a T650MS treadmill (SportsArt, Tainan City, Taiwan). The BWSTT protocol was based on our previous study 6 ) and included the following parameters: 20% body weight unloading; treadmill speed to the maximum steady state walking speed for each individual; training up to a self-reported fatigue level on the 20-point Borg scale.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation